O conceito de democracia no pensamento de Rosa Luxemburgo - Oliveira, Aislan Jonis Estevam Bertolucci de (2018)
The purpose of this dissertation is to apprehend the construction of the concept of democracy in the thought of Rosa Luxemburg. It should be noted at the outset that, if on the one hand, the Polish Marxist does not present a systematic theory about such a concept, from another, it is possible to extract from the set of his work elements that corroborate to its conformation. As we will try to demonstrate, the substantive democracy devised by Rosa Luxemburg is not confused with the limits of bourgeois-parliamentary democracy – the latter understood as a crude caricature. Thus, democracy of a new type is the one that is being constituted within the public-proletarian space as a result of the everyday experiences of the working masses in the struggle against the exploitation of capitalist classes. In this sense, the emergence of the Councils of Workers and Soldiers in the German revolutionary process of 1918 would catch the attention of our author. Although Luxembourg has not had time to observe with more precision the development of the councils – had been murdered in early 1919 – she took it for granted that these, by unifying the political and economic sphere, constituting the power of the working class would represent socialist democracy.